Children and young people's perspectives and experiences of a community wheelchair basketball club and its impact on daily life. (February 2020) - Moss, Philippa; Lim, Kee Hean; Prunty, Mellissa; Norris, Meriel
Introduction: Although the benefits of physical activity are widely recognised, levels of inactivity are considerably higher for children and young people with disabilities than those without. Young people with disabilities struggle to access inclusive opportunities and there is a lack of research surrounding users' experiences of disability sport more generally. This research aimed to explore members' experiences of a community-based wheelchair basketball club and its impact on daily life. Method: Semi-structured interviews were conducted with 11 disabled and able-bodied members of the club (aged 6–25 years) to gain an in-depth understanding of their experiences. Findings: Inductive thematic analysis identified an overarching theme of 'wheelchair basketball elicits strong emotions' and four main themes of 'positive social interactions', 'benefitting health and independence', 'changing perceptions of disability' and 'a meaningful occupation that opens doors'. Participants reported positive experiences of wheelchair basketball, which improved their physical and mental health whilst increasing opportunities for socialisation and encouraging acceptance of disability. Conclusion: The findings have implications at individual, organisational and societal levels, and provide some justification for the role of occupational therapy in disability sport. The findings demonstrate the potential for inclusive community sports clubs to improve health and social outcomes for individuals, regardless of disability.